The physiology of motor learning - Hellebrandt, F. A. (Readings in motor learning, 1972)
Total actions (e.g., those to be used in a competitive setting) need to be trained. It is highly unlikely that partial or isolated training of movement segments will replicate the unit function in the total action. Thus, once techniques (total response patterns) are being refined, partial practices will serve no purpose other than to learn another movement. There will be no integration of the partial practice movement into the total response movement. The skill content of practices has to mimic that of competitive requirements if beneficial training time is to be experienced. It is wrong to practice something with good intent (e.g., "I hope it will benefit the performance") without being able to justify and demonstrate correlated transfer to a competitive skill. If this dictum is not adhered to then much practice will be wasted or even counter-productive. It is quite possible that movements practiced could be so irrelevant that their impact on hoped for competition-specific movements will be so destructive that performance will be worse than if no skill practice had been entertained.